Proceedings of the 11th International Conference on Informatics in Control, Automation and Robotics 2014
DOI: 10.5220/0005102407770782
|View full text |Cite
|
Sign up to set email alerts
|

WSN-based near Real-time Environmental Monitoring for Shelf Life Prediction through Data Processing to Improve Food Safety and Certification

Abstract: This position paper aims to support a control technique in the perishables goods supply-chain through a combination of near real-time wireless sensor network (WSN) for environmental monitoring and further data processing to predict the shelf life of the product. This approach returns a low cost, versatile and efficient tool that can significantly improve the safety and food certification through the organoleptic qualities control using three different sensors, i.e. temperature, light and humidity. In this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…A number of literature studies [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] have showed that, among the extracted environmental variables, the temperature is the parameter that significantly emphasizes worsening food quality.…”
Section: Shelf-life Predictionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of literature studies [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] have showed that, among the extracted environmental variables, the temperature is the parameter that significantly emphasizes worsening food quality.…”
Section: Shelf-life Predictionmentioning
confidence: 99%
“…Since the Arrhenius law parameters are typically determined with non-linear regression of empirical data, such as the one in [ 6 , 21 , 22 ], in the following, we will insert the kinetic parameters, provided by a tomatoes-centered study, in a general formula for k rate derivation, suitable for any temperature: with k ref : k value at the dedicated reference temperature T ref .…”
Section: Shelf-life Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…The solution aims to be a diagnostic tool for the early detection ofthe disease, as well as a useful clinical support tool for monitoring the therapy impact. Future perspectives include the design and fabrication of an Application Specific Integrated Circuit (ASIC) [23][24][25][26][27][28][29][30], the use of biocompatible and flexible electronics in order to increase the wearability degree of the system [31,32] and the optimization of the wireless network [33][34][35][36].…”
Section: Considering the Single Muscle-based Indexes Pd Subjectsmentioning
confidence: 99%